Rote Liste der Weberknechte Deutschlands (Arachnida: Opiliones) - Bliss, Peter; Martens, Jochen; Blick, Theo (Arachnologische Mitteilungen, 1996)

(untitled)
List of endangered harvestmen species of Germany (Red Data Book) (Arachnida: Opiliones)